Biocompatible Cs2PtX6 (X = Cl, Br, I) Vacancy Ordered Perovskites and Shewanella oneidensis MR‑1 Bacteria Hybrid for Potential Photocatalytic Solar Fuel Production - Shinde, Shweta; Hamdan, Muhammed; Bhalla, Prerna; Chandiran, Aravind Kumar (ACS Engineering Au, 2024)
Semiconductor-bacterial hybrid systems have been shown to be effective for photochemical conversion. The combination of two systems delineates the light absorption from the catalytic ability, wherein a semiconductor absorbs light, generating an electron–hole pair, followed by the transfer of photogenerated charges to catalytically active bacteria that assume the roles of carrying out redox reactions. The halide perovskite materials possess excellent optoelectronic properties and, if they exhibit biocompatibility with microorganisms, shall provide an opportunity to carry out environmentally important redox reactions including carbon dioxide conversion to value added products. In this work, we report the biocompatibility of panchromatic visible light absorption and stable vacancy ordered halide perovskite (VOP), Cs2PtX6 (X = halide) with Shewanella oneidensis MR-1 nonphotosynthetic bacterium. This microbe is shown to grow in culture media containing VOP, and the growth rate is found to be unaffected by the presence of semiconductor media. Although Shewanella oneidensis MR-1 is a well-known metal-reducing bacteria, in this work, we find that the vacancy ordered perovskite materials remain intact with this bacterium. With constraint-based metabolic modeling, we report that this biohybrid system shall potentially be used for solar energy conversion of water and carbon dioxide to hydrogen and formate, respectively.